2022
DOI: 10.1038/s41396-022-01313-9
|View full text |Cite
|
Sign up to set email alerts
|

Flavobacterial exudates disrupt cell cycle progression and metabolism of the diatom Thalassiosira pseudonana

Abstract: Phytoplankton and bacteria form the base of marine ecosystems and their interactions drive global biogeochemical cycles. The effects of bacteria and bacteria-produced compounds on diatoms range from synergistic to pathogenic and can affect the physiology and transcriptional patterns of the interacting diatom. Here, we investigate physiological and transcriptional changes in the marine diatom Thalassiosira pseudonana induced by extracellular metabolites of a known antagonistic bacterium Croceibacter atlanticus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Recently, there have been documented isolations of pathogenic bacteria that can infect other phytoplankton groups such as diatoms [ 34 , 35 ]. Therefore, the aerial infection mechanism of bacterial pathogens may have a broad implication to diverse algal–bacteria interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been documented isolations of pathogenic bacteria that can infect other phytoplankton groups such as diatoms [ 34 , 35 ]. Therefore, the aerial infection mechanism of bacterial pathogens may have a broad implication to diverse algal–bacteria interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, Flavobacteriaceae and Phaeocystis may have a mutually beneficial symbiotic relationship because Flavobacteriaceae maintained a higher abundance in the pre-stage of Phaeocystis bloom ( Figures 4B , 7 ). Recent evidence documented that Flavobacterial exudates can change the morphology of algal cells, which causes algal cells to become larger and secrete more carbohydrates ( Bartolek et al, 2022 ). Current phylogenetic analyses of the marine microbiome by experimental and natural phytoplankton blooms suggest that members of Flavobacteriaceae (i.e., Polaribacter , Robiginitalea ) are commonly associated with the bloom development of the Phaeocystis population ( Wemheuer et al, 2015 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory study demonstrated that C. atlanticus directly attaches to diatoms and inhibits cell division. Moreover, C. atlanticus exudates caused increases in intra-and extracellular carbon in Thalassiosira pseudonana, suggesting that bacterial antagonists can modulate host metabolism to support their growth (Bartolek et al, 2022).…”
Section: Cryptic Bacterial Pathogens Of Diatoms Peak During Senescenc...mentioning
confidence: 99%